DNA methylation changes measured in pre‐diagnostic peripheral blood samples are associated with smoking and lung cancer risk. Issue 1 (11th October 2016) - Baglietto, Laura; Ponzi, Erica; Haycock, Philip; Hodge, Allison; Bianca Assumma, Manuela; Jung, Chol‐Hee; Chung, Jessica; Fasanelli, Francesca; Guida, Florence; Campanella, Gianluca; Chadeau‐Hyam, Marc; Grankvist, Kjell; et al.
Abstract : DNA methylation changes are associated with cigarette smoking. We used the Illumina Infinium HumanMethylation450 array to determine whether methylation in DNA from pre‐diagnostic, peripheral blood samples is associated with lung cancer risk. We used a case‐control study nested within the EPIC‐Italy cohort and a study within the MCCS cohort as discovery sets (a total of 552 case‐control pairs). We validated the top signals in 429 case‐control pairs from another 3 studies. We identified six CpGs for which hypomethylation was associated with lung cancer risk: cg05575921 in the AHRR gene ( p ‐valuepooled  = 4 × 10 −17 ), cg03636183 in the F2RL3 gene ( p ‐valuepooled  = 2 × 10 − 13 ), cg21566642 and cg05951221 in 2q37.1 ( p ‐valuepooled  = 7 × 10 −16 and 1 × 10 −11 respectively), cg06126421 in 6p21.33 ( p ‐valuepooled  = 2 × 10 −15 ) and cg23387569 in 12q14.1 ( p ‐valuepooled  = 5 × 10 −7 ). For cg05951221 and cg23387569 the strength of association was virtually identical in never and current smokers. For all these CpGs except for cg23387569, the methylation levels were different across smoking categories in controls ( p ‐valuesheterogeneity  ≤ 1.8 x10 − 7 ), were lowest for current smokers and increased with time since quitting for former smokers. We observed a gain in discrimination between cases and controls measured by the area under the ROC curve of at least 8% ( p ‐values ≥ 0.003) in former smokers by adding methylation at the 6 CpGs into risk prediction models including smoking status and number of pack‐years. Our findings provide convincing evidence that smoking and possibly other factors lead to DNA methylation changes measurable in peripheral blood that may improve prediction of lung cancer risk. Abstract : What's new? It is well known that smoking can cause lung cancer but the concept that it might do so by changing DNA methylation is only emerging. Here the authors identify six sites of methylation (CpGs), where methylation levels were associated with lung cancer risk after adjusting for smoking, current or former. Methylation of five of the CpGs was lowest in current smokers and increased in former smokers with time since quitting, supporting the growing evidence that smoking may lead to DNA methylation changes measurable in peripheral blood and useful as predictive markers for lung cancer risk, especially in former smokers.